Analysis Of Classroom Interaction In Speaking Class At A Senior High School In Bandar Lampung - Hery Yufrizal; Nanda Riyanti (LINGUISTIKA, 2011)
This study compares patterns of interactions among teachers and students in all English speaking class by using three different newspaper topics: political, economy and entertainment. The subject of the research was 31 students of a senior high school in Bandar Lampung.The result shows that three were differences in the patterns of interaction when learners were given three different newspaper article topics. The differences were found in terms of the patterns of interactions among teacher-students, and students- students as well at kinds of interactional contribution categories.This suggests that using various topics from various sources of materials provided good stimulus for learners to practice their English in the classroom. The closer the topic to the learners daily interest the more they will likely to actively involve in the interactions.